Do Migrant Residents Really Achieve Health Equity by Obtaining Urban Hukou? A Comparative Study on Health Service Utilization and Urbanization in Central China - Min, Rui; Fang, Zi; Zi, Chunyan; Tang, Changmin; Fang, Pengqian (Frontiers in Public Health, 2022)
Introduction With more than 120 million rural-to-urban migrants, urbanization of the rural population requires deeply exploration in China. Objective This study focused on settled citizens who obtained urban Hukou (household registration) during urbanization and investigated their perceptions of health services in China. Method A cross-sectional comparison study with an original, closed questionnaire was conducted in two major cities of Hubei, central China, covering health status and both the satisfaction with and utilization of health services. In total, 863 residents with urban Hukou participated in this study; migrants formed the study group and original city residents formed the control group. Propensity score matching (PSM) was used to reduce choice bias in the analysis steps. Besides basic description of the data, ordinary least squares regression (OLS regression) was used to discover the relationship between basic demographic indicators and health expenditure. Results PSM yielded 290 effective pairs for analysis. The results indicated an improvement in health status for migrant residents (study group) with a higher average score of self-reported health status and lower prevalence of chronic diseases than the control group. These scores were also better than the standard urban level in central China. The study group showed a higher clinic visit utility (69.63%), lower hospitalization utility (8.28%), less convenience of health service utility, and lower health expenditure than the control group. For the study group, the biggest difference was observed in satisfaction with health service costs, which was the least improved aspect after they obtained urban Hukou. The regression results demonstrated that age, family size, living expenditures, and marital status impacted health costs in the overall model and the influences of these factors differed between the study and control groups. Conclusions Obtaining urban Hukou helps newly urban residents meet their health service needs and receive equal access to health services. However, after obtaining urban Hukou, migrants also face great pressure in terms of health consumption. This study therefore offers guidance on the next steps for progressing China’s urbanization.